Hydride generation atomic absorption spectrometric determination of bismuth after separation and preconcentration with modified alumina. Issue 4 (16th January 2015) - Shakerian, Farid; Haji Shabani, Ali Mohammad; Dadfarnia, Shayessteh; Kazemi Avanji, Mahboubeh
<x xml:space="preserve">Abstract</x> A simple and sensitive method has been developed for the trace determination of bismuth in aqueous samples by a combination of solid‐phase extraction and hydride generation atomic absorption spectrometry. The method is based on the use of a column packed with 2‐mercaptobenzothiazole immobilized on sodium dodecyl sulfate coated alumina. Different parameters influencing the separation and preconcentration of bismuth such as pH, sample volume, type, and concentration of eluent, and the flow rate of sample and eluent were studied. A sample volume of 500.0 mL resulted in a preconcentration factor of 100. The precision (relative standard deviation, N = 10) at the 300 ng/L level and the limit of detection (3s) were found to be 2.3% and 12 ng/L, respectively. The developed method was successfully applied to the determination of bismuth in natural water samples and two certified reference materials.